2008
DOI: 10.1007/bf03182199
|View full text |Cite
|
Sign up to set email alerts
|

Vortex dynamics and entrainment mechanisms in low Reynolds orifice jets

Abstract: Classical planar 2D-PIV measurements and time-resolved visualizations enriched by low-level processing are used for the reconstruction of the Kelvin-Helmholtz vortex passing in the near field of a circular and a 6-lobed orifice jet flow. In the circular jet, the entrainment is produced in the braid region, being interrupted in the presence of the Kelvin-Helmholtz ring. The latter compresses the streamwise vortices and alters their self-induction role. Conversely, the 6-lobed orifice geometry allows the cutting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 34 publications
3
24
0
Order By: Relevance
“…In order to obtain the same initial conditions as in the previous study (Nastase and Meslem 2008), air jet facility is conserved (Fig. 1a).…”
Section: Methodsmentioning
confidence: 98%
See 4 more Smart Citations
“…In order to obtain the same initial conditions as in the previous study (Nastase and Meslem 2008), air jet facility is conserved (Fig. 1a).…”
Section: Methodsmentioning
confidence: 98%
“…A comparison between images from classical PIV measurements and from TR visualizations, using a low-level image-processing algorithm, allowed the reconstruction of a pseudo-time resolved PIV fields sequence corresponding to one period of K-H vortex passing. This procedure allowed a quantitative approach of a particular phenomenon, in the circular jet and in the daisy jet having the same low initial Reynolds number (Nastase and Meslem 2008). For the circular jet, we found that the entrainment is produced in the braid region where the streamwise structures develop.…”
mentioning
confidence: 97%
See 3 more Smart Citations